Modulating the charge injection in organic field-effect transistors: fluorinated oligophenyl self-assembled monolayers for high work function electrodes1. Issue 13 (7th April 2015) - Fenwick, Oliver; Van Dyck, Colin; Murugavel, Kathiresan; Cornil, David; Reinders, Federica; Haar, Sébastien; Mayor, Marcel; Cornil, Jérôme; Samorì, Paolo
<x xml:space="preserve">Abstract</x> Experiment and theory reveals origin of work function and contact resistance of fluorinated oligophenylthiol-treated electrodes in organic transistors.